Explicit limit cycles of a cubic polynomial differential systems - BENDJEDDOU , Ahmed; BOUKOUCHA, Rachid (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper, we determine sufficient conditions for a cubic polynomial differential system to possess an algebraic, non-algebraic limit cycles, explicitly given. Concrete examples exhibiting the applicability of our result is introduced. Mathematics Subject Classification (2010): 34A05, 34C05, 34CO7, 34C25.